Effect of incorporation of herbal essential oil on anti-oxidative, instrumental color and sensorial attributes of burfi - Prasad, Writdhama G; Khamrui, Kaushik; Badola, Richa; Gupta, Hari Ram (Indian Journal of Dairy Science, 2018)
Herbs contain high amount of polyphenols which possess high anti-oxidative attributes. The present study was undertaken with the objective to increase anti-oxidative activity in burfi by incorporating herbal essential oil into it. Turmeric, ginger and cardamom essential oils were incorporated into burfi from 100-600ppm levels. Anti-oxidative activity was measured in terms of total phenolic content and free radical (ABTS and DPPH) free radical scavenging activity. Significant (p<0.05) increase in anti-oxidative activity in burfi was observed with increase in levels of essential oils. Highest anti-oxidative activity was observed from turmeric essential oil added burfi, followed by ginger and least activity was observed in burfi sample added with cardamom essential oil. However, instrumental color values remained unaffected (p>0.05) upon essential oil addition. Sensory evaluation of herbal burfi samples revealed decreasing order of preference for burfi with increasing herbal essential oil level. Significant (p<0.05) decrease in scores were observed in samples added with > 100 ppm of turmeric essential oil, >200 ppm ginger essential oil and >300 ppm essential oil. Thus, Turmeric essential oil at 100ppm, Ginger essential oil at 200ppm and Cardamom essential oil at 300ppm were found to optimum for incorporation into burfi at which total phenolic content in burfi were 0.743 µgGAE/g, 0.656 µgGAE/g and 0.588 µgGAE/g, ABTS free radical scavenging activity was 35.93%, 20.47% and 17.40%, and DPPH free radical scavenging activity was 15.34%, 13.11% and 11.43%, respectively. The results obtained will be helpful for developing herbal extract added traditional Indigenous dairy sweetmeats.